login
a(n) = A068336(n+1) - 1.
0

%I #9 Feb 20 2022 15:12:08

%S 1,3,5,9,11,19,21,31,37,51,53,79,81,105,121,153,155,207,209,267,293,

%T 349,351,453,465,549,587,699,701,875,877,1031,1089,1247,1279,1547,

%U 1549,1761,1847,2137,2139,2529,2531,2887,3041,3395,3397,3973,3995,4501

%N a(n) = A068336(n+1) - 1.

%C Row sums of triangle A160183.

%C Equals M * V, where M = A051731, the inverse Mobius transform and V = A068336: (1, 2, 4, 6, 10, 12, ...).

%F a(n) = A068336(n+1) - 1

%e a(6) = 19 = A068336(7) - 1 = (20 - 1).

%e a(6) = 19 = (1, 1, 1, 0, 0, 1) dot (1, 2, 4, 6, 10, 12) = (1 + 2 + 4 + 0 + 0 + 12); where (1, 1, 1, 0, 0, 1) = row 6 of triangle A051731.

%Y Cf. A068336 (Mobius transform), A160183, A051731, A054525.

%K nonn

%O 1,2

%A _Gary W. Adamson_, May 29 2013